Envisioning scholar-practitioner collaborations : communities of practice in education and sport - Van Rheenen, Derek; DeOrnellas, Jean Marie (Research focus on education and sport, 2018)
"Envisioning Scholar-Practitioner Collaborations : Building Communities of Practice in Education and Sport presents a collection of case studies of collaborations between scholars and practitioners dedicated to both the generation of new knowledge and innovative best practices at the nexus of education and sport. This inaugural text in a series sponsored by the Research Focus on Education and Sport Special Interest Group of the American Educational Research Association seeks to reveal a number of educational spaces in which this critical work takes place. The volume, comprising ten unique collaborations, outlines the important intellectual and social work of scholar-practitioners at the intersection of institutional sport and education at a variety of sites, both in school and in non-school settings. Each of these chapters has a unique set of research questions, programmatic goals and findings. For the purpose of this book, however, contributing have described the nature of their collaborations--for whom and by whom these collaborations are forged--such that the "findings" are presented as lessons learned from the process of collaboration"--